(untitled) - Courter, Gini (San Francisco, 1999)
Written for business people who really want to go beyond the basics, this definitive guide on Outlook quickly moves into intermediate and advanced features. Challenging topics include security, email decoding, using Outlook with the Web, integrating Outlook with other Office applications, compatibility with email services, setting up Outlook for a LAN and as an Exchange Server client, and much more. With a comprehensive troubleshooting section, this is the Outlook book users will turn to for answers to the tough questions. It covers Outlook for stand-alone, LANs and Exchange Server environments, plus Outlook Express.
Keywords: Time management,Personal information management,Electronic mail systems,Quản lý thời gian,Quản trị thông tin nhân sự,Hệ thống thư điện tử; Computer programs,Computer programs,Chương trình máy tính,Chương trình máy tính